2020
DOI: 10.1080/1343943x.2020.1766361
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci for water uptake of rice under aerobic conditions

Abstract: Root development in rice (Oryza sativa L.) plays a key role in water uptake (WU) and water use efficiency (WUE) in water-saving technologies such as aerobic cultivation. Traits that contribute to root development are controlled by many complex quantitative trait loci (QTLs). Understanding the genetic mechanisms of root traits related to WUE is strategic in breeding for aerobic cultivation. Here, we mapped QTLs for root traits in double haploid lines derived from a cross between a japonica paddy rice, Koshihika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Consequently, this confirms that plants with small roots have a relatively higher WUE, especially under drought stress (Figure 5A,C), which correlates with previous research [18]. Some studies have suggested that the root system is an important index to determine crop WUE [55,56]. Our study showed that the size of the crop root system strongly influences WUE.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, this confirms that plants with small roots have a relatively higher WUE, especially under drought stress (Figure 5A,C), which correlates with previous research [18]. Some studies have suggested that the root system is an important index to determine crop WUE [55,56]. Our study showed that the size of the crop root system strongly influences WUE.…”
Section: Discussionsupporting
confidence: 90%
“…The improvement of root function is necessary to increase water uptake by the plant (Meister et al, 2014). The root system is an important index to determine crop water-use efficiency (WUE) (Sreeman et al, 2018;Corales et al, 2020), which is vital for sustaining productivity and minimising crop water utilisation. Passioura (1983) proposed that crop yield and WUE do not necessarily increase with the size of the root system.…”
Section: Introductionmentioning
confidence: 99%